Depicting Berlin’s Atmospheres: Phenomenographic Sketches - Maxime Le Calvé; Olivier Gaudin (Ambiances)
This article proposes an ethno-phenomenographic record combining writing and drawing. It examines a few contemporary atmospheres of the city of Berlin. We describe a selection of specific situations from the angle of sensorial experience and contextualize them with sociological, geographical and historical elements. Tackling some atmospheres characteristic of a city at a certain period of its history is not the same as trying to grasp the ways of living in it; therefore, our approach is neither sociological nor geographical per se. Elaborating on four specific cases and reflecting from our own perspectives, we will examine the hypothesis of a fragmentation of Berlin’s atmospheres, exploring the ambivalent meanings of such assessment. The method is ethnographic: we base our descriptions on direct observation and we confront our respective experiences in places physically circumscribed by architecture and urban forms, interspersed with multiple presences and interactions during the observed time sequences. The overall objective is also cooperative and interdisciplinary: the sharing of our own points of view and perceptions through drawing, speaking and writing as processes of building an account of urban phenomena, without erasing differences in perspective. Through this very partial selection of seemingly representative atmospheres over one Berlin summer, we sketch a nuanced portrait of the city that does not exclude criticism.